Evaluation of jackfruit (Artocarpus heterophyllus) seed powder-based pasta- a case study - Kumar, Kapil; Kumar, Pranav; Kumar, Vinay; Panwar, Sanjeev; Kaushik, Himani; Tomar, Sonia (Current Horticulture, 2025)
Jackfruit seeds, comprising 10-15% of the fruit, are nutrient-rich with high protein, carbohydrate, and mineral content. Analysis of jackfruit seed flour (JSF) revealed substantial protein (13.49%) and essential minerals like potassium and magnesium. The JSF, with high water and oil absorption capacities, enhanced pasta's nutritional value and texture when added in proportions of 5-20%, with 10% substitution preferred for optimal consumer satisfaction. Jackfruit seeds offer significant potential as a valuable resource in addressing food security challenges, particularly in densely populated regions. Their conversion into flour provides a sustainable solution to mitigate waste during seasonal abundance. With rich nutritional content and favourable functional properties, jackfruit seed flour enhances the nutrient profile and quality of various food products, such as pasta, while maintaining consumer acceptability. Moreover, the unique twist of roasting jackfruit seeds in sand adds a distinctive flavour and texture to dishes, contributing to culinary innovation. Embracing such natural processes not only enhances taste but also preserves essential nutrients, underscoring the importance of sustainable food practices.